Algorithm-based approach to headache - Jayaprakash R. Ravan; Jigyansa I. Pattnaik; Swayanka Samantray (Journal of Family Medicine and Primary Care)
One of the most commonly encountered scenarios in any healthcare setting is a patient presenting with a headache. Yet, the assessment, diagnosis and treatment of headache disorders can be challenging and burdensome for even specialist doctors in medicine, psychiatry, oto-rhinology, neurology and so on. Apart from saving patient’s and doctor’s time as well as money, this article will buy leading time for better outcome and management of certain difficult headache disorders. The aim of this review is to simplify the approach to headache diagnosis for an early and proper referral. Literature search was done on PubMed and Google Scholar using key words. Only studies which were in English were considered. Sixty-one articles published from 1975 to 2022 were reviewed after screening for inclusion and exclusion criteria. It is very essential that a primary care physician is aware of the classification of headache. Red flag signs of high-risk headaches are essential for proper referral. It is also essential that we rule out secondary headaches as they are more life threatening. Vulnerable populations such as geriatric and paediatric populations require expert attention in case of headache disorders.